SUSTAINABLE DEVELOPMENT GOALS AND THE CATHOLIC CHURCH: Catholic Social Teaching and the UN’s Agenda 2030: Katarzyna Cichos, Jarosław A. Sobkowiak, Ryszard F. Sadowski, Beata Zbarachewicz, Radosław Zenderowski, and Stanisław Dziekoński, eds. - Huo, Yanyan (Journal of Dharma, 2021)
Sustainable Development Goals and the Catholic Church is an exceptional effort to create a synergy between effective policy making and its implementation through the identification of convergent areas between Agenda 30 and Catholic social teaching in order to achieve the 17 Sustainable Development Goals. This monograph puts forth the evolution of Catholic approach towards the contemporary realities of social life, and highlights superbly the potential of Catholic Church in achieving the goals set by Agenda 30. Through a panel of 55 authors of different scientific disciplines, this work aims to provide readers with a better, more intuitive outlook on and understanding the multifaceted nature of individual sustainable development goals.